Recognizing and Confronting State Subjectivity in Asylum Adjudications - Barry-Murphy, Emily C.; Stephenson Jr., Max (Refuge: Canada's Journal on Refugees, 2015)
United States law charges America’s asylum officers with providing humanitarian protection for refugees while simultaneously securing the nation from external threats. This mandate requires that asylum officers balance potentially conflicting claims as they seek to ensure just treatment of claimants. This article explores how officers charged with that responsibility can develop a regime-centred subjectivity that often conditions them to view applicants with fraud and security concerns foremost in mind. This analysis also examines the potential efficacy of practical strategies linked to aesthetic, cognitive, affective, and moral imagination that may allow officials to become more aware of their statecentred subjectivity and how it influences their perceptions of threats to national security and to fraud. This analysis encourages adjudication officers to strive for a more nuanced understanding of what constitutes fraud and national security concerns and what are instead presuppositions created by the United States population-protection agenda.